DNA barcoding and forensic entomology: a molecular approach for Diptera species' identification - Rolo, Eva Sofia Alves, 1986- (2010)
Tese de mestrado em Biologia (Biologia Humana e Ambiente),Universidade de Lisboa, Faculdade de Ciências, 2010